High-intensity focused ultrasound technology as a non-surgical alternative to face lifting - Smoczok, Michał; Leonik, Szymon; Bergler-Czop, Beata (Dermatology Review/Przegląd Dermatologiczny, 2022)
Treatments improving the tension of the facial skin are an important branch of aesthetic dermatology. There is an ongoing increase in medical options of non-invasive alternatives to surgical face lifting. One of them is the high-intensity focused ultrasound (HIFU) technology. The evaluation of the efficacy of this technique shows a significant improvement in the condition of the facial skin. However, the durability of the resulting changes is still debatable. Compared to other procedures, the high-intensity focused ultrasound technology has the benefit of a very good safety profile and short recovery period. Therefore, it is worth considering as an possible alternative to surgical methods. Key words: high-intensity focused ultrasound ablation, facelift, ultrasonic therapy.